Respuesta :
2x^2 - 12xy - 32y^2 =
2(x^2 - 6xy - 16y^2) =
2(x - 8y)(x + 2y)
so the coefficient B is 2
2(x^2 - 6xy - 16y^2) =
2(x - 8y)(x + 2y)
so the coefficient B is 2
2x^2 -12xy -32 y^2
= 2 (x^2 -6xy -16y^2)
= 2 (x^2 -8xy +2xy -16y^2)
= 2 {x (x-8y)+ 2y (x-8y) }
= 2 { (x+2y)(x-8y) }
Given that:
2 { (x-8y) (x+2y)} = 2(x − 8y)(x + By)
So, B = 2
= 2 (x^2 -6xy -16y^2)
= 2 (x^2 -8xy +2xy -16y^2)
= 2 {x (x-8y)+ 2y (x-8y) }
= 2 { (x+2y)(x-8y) }
Given that:
2 { (x-8y) (x+2y)} = 2(x − 8y)(x + By)
So, B = 2